Chemotherapy Resistance in B-ALL with Cryptic NUP214-ABL1 Is Amenable to Kinase Inhibition and Immunotherapy. (4th February 2022) - Nardi, Valentina; McAfee, Steven L; Dal Cin, Paola; Tsai, Harrison K; Amrein, Philip C; Hobbs, Gabriela S; Brunner, Andrew M; Narayan, Rupa; Foster, Julia; Fathi, Amir T; Hock, Hanno
Abstract: BCR-ABL1 kinase inhibitors have improved the prognosis of Philadelphia-chromosome-positive (Ph + )-acute lymphoblastic leukemia (ALL). Ph-like (or BCR-ABL1 -like) ALL does not express BCR-ABL1 but commonly harbors other genomic alterations of signaling molecules that may be amenable to therapy. Here, we report a case with a NUP214-ABL1 fusion detected at relapse by multiplexed, targeted RNA sequencing. It had escaped conventional molecular work-up at diagnosis, including cytogenetic analysis and fluorescence in situ hybridization for ABL1 rearrangements. The patient had responded poorly to initial multi-agent chemotherapy and inotuzumab immunotherapy at relapse before the fusion was revealed. The addition of dasatinib targeting NUP214-ABL1 to inotuzumab resulted in complete molecular remission, but recurrence occurred rapidly with dasatinib alone. However, deep molecular remission was recaptured with a combination of blinatumomab and ponatinib, so he could proceed to allotransplantation. This case illustrates that next-generation sequencing approaches designed to discover cryptic gene fusions can benefit patients with Ph-like ALL. Abstract : Next-generation sequencing approaches designed to discover cryptic gene fusions can be of benefit to patients with acute lymphoblastic leukemia. This article reports the case of a patient with an NUP214-ABL1 fusion detected by RNA sequencing at relapse.